Implementasi Program Kampus Mengajar 7 Dalam Upaya Meningkatkan Kemampuan Literasi Dan Numerasi Siswa SD Inpres Bangkala III Kecamatan Manggala Kota Makassar - Afifah Irwan; Hurriah Ali Hasan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The purpose of this teaching campus initiation is to improve the reading and arithmetic skills of elementary school students. The pretest results show that the level of reading and arithmetic skills of children at SD Inpres Bangkala III, Manggala sub-district, is relatively low. The Teaching Campus Program Batch 7 was implemented as an effort to address this problem. Using qualitative methodology and a case study focus, the researcher provided comprehensive knowledge of the implementation of the program in the classroom. The research subjects were fifth grade students at SD Inpres Bangkala III, Manggala sub-district, Makassar City along with the teachers and principal. Information was collected through observation, interviews. Before and after the implementation of the program, the success of the data obtained was assessed using qualitative analysis. These results show that the learning methods that the teaching campus applied to students improved students' reading and comprehension skills. Students' average scores on post-test questions have increased, according to the numeracy evaluation data. This includes things like parental support, creative teaching strategies such as project-based learning and technology integration, and the active participation of principals and teachers. Improved secondary school education has been positively impacted by this initiative. The Campus Teaching Program Batch 7 at SD Inpres Bangkala III, Manggala sub-district has proven effective in improving students' literacy and numeracy skills. Parental support, creative teaching strategies and teacher engagement play a role in the success of this program. The development of learning strategies will benefit from the above results. The implementation of this program is a useful example of overcoming difficult barriers in education.